Academic Resilience among Final-Year Health Professional Students: Programmatic and Gender Variations in Indonesia - Atik Ulinuha; Setyani Alfinuha (Academica: Journal of Multidisciplinary Studies, 2025)
Academic resilience is a crucial attribute for students in health-related disciplines to adapt and thrive amid high academic and clinical demands. Objective: This study aims to analyze the level of academic resilience among final-year students across various health disciplines, identify variations in resilience levels, and explore the implications for developing more targeted academic support and mental health interventions. Method: This study employed a descriptive quantitative approach using a cross-sectional survey design. Data were collected through a structured questionnaire adapted from a validated scale, the Academic Resilience Scale (ARS-6). The study population consisted of 272 final-year undergraduate and diploma students from nine health-related study programs at a private higher education institution in Indonesia, selected through convenience sampling. The collected data were analyzed using descriptive statistical techniques. Results: The findings indicate that the majority of respondents (84.92%) demonstrated high levels of academic resilience. Male students tended to exhibit higher mean resilience scores (38.15) and more stable distributions compared to female students (35.15). In terms of study programs, undergraduate Dentistry and diploma Midwifery recorded the highest average resilience scores, whereas undergraduate Nursing and undergraduate Pharmacy showed the lowest. Conclusion: Although most final-year students in health-related programs exhibit high academic resilience, significant variations exist across study programs and between genders.